In vivo treatment with varespladib, a phospholipase A2 inhibitor, prevents the peripheral neurotoxicity and systemic disorders induced by Micrurus corallinus (coral snake) venom in rats. (1st March 2022) - Silva-Carvalho, Rosimeire; Gaspar, Matheus Z.; Quadros, Luiz H.B.; Lobo, Luís G.G.; Rogério, Letícia M.; Santos, Najla T.S.; Zerbinatti, Maria C.; Santarém, Cecília L.; Silva, Elisangela O.; Gerez, Juliana R.; Silva Jr., Nelson J.; Lomonte, Bruno; et al.
Highlights: Varespladib efficiently prevents the M. corallinus venom-induced neuromuscular paralysis. Varespladib attenuates the M. corallinus venom-induced inflammatory responses and renal damage. Varespladib produces discrete local protection even combined with an antivenom. Varespladib acts synergistically with antivenom to prevent M. corallinus venom-induced systemic effects. Abstract: In this study, we investigated the action of varespladib (VPL) alone or in combination with a coral snake antivenom (CAV) on the local and systemic effects induced by Micrurus corallinus venom in rats. Adult male Wistar rats were exposed to venom (1.5 mg/kg – i.m.) and immediately treated with CAV (antivenom:venom ratio 1:1.5 'v/w' – i.p.), VPL (0.5 mg/kg – i.p.), or both of these treatments. The animals were monitored for 120 min and then anesthetized to collect blood samples used for haematological and serum biochemical analysis; after euthanasia, skeletal muscle, renal and hepatic tissue samples were collected for histopathological analysis. M. corallinus venom caused local oedema without subcutaneous haemorrhage or apparent necrosis formation, although there was accentuated muscle morphological damage; none of the treatments prevented oedema formation but the combination of CAV and VPL reduced venom-induced myonecrosis. Venom caused neuromuscular paralysis and respiratory impairment in approximately 60 min following envenomation; CAV alone did not prevent the neurotoxic action, whereas VPL alone prevented neurotoxic symptoms developing as did the combination of CAV and VPL. Venom induced significant increase of serum CK and AST release, mostly due to local and systemic myotoxicity, which was partially prevented by the combination of CAV and VPL. The release of hepatotoxic serum biomarkers (LDH and ALP) induced by M. corallinus venom was not prevented by CAV and VPL when individually administered; their combination effectively prevented ALP release. The venom-induced nephrotoxicity (increase in serum creatinine concentration) was prevented by all the treatments. VPL alone or in combination with CAV significantly prevented the venom-induced lymphocytosis. In conclusion, VPL shows to be effective at preventing the neurotoxic, nephrotoxic, and inflammatory activities of M. corallinus venom. In addition, VPL acts synergistically with antivenom to prevent a number of systemic effects caused by M. corallinus venom.